Diseño y construcción de un sistema de alimentación automático para peces de 200 kg de capacidad, provisto por energía solar fotovoltaica para la granja piscícola Asociación Propaz en Mesetas (Meta). (2021)
Currently, the Propaz association carries out the activity of feeding fish manually, a worker feeds the different stages of the culture with the frequency of 8 to 6 servings in a day, at an interval of 1 hour and a half each. A disadvantage of this way of feeding is that the feeding time is not constant and it is not possible to comply with the rationale of the food to give it at a certain time, this affects the weight gain of the animals. In addition, the worker can perform another activity while the machine performs the work.